2014
DOI: 10.1007/s00787-014-0614-z
|View full text |Cite
|
Sign up to set email alerts
|

Brain changes in early-onset bipolar and unipolar depressive disorders: a systematic review in children and adolescents

Abstract: Pediatric bipolar disorder (BD) and unipolar disorder (UD) share common symptomatic and functional impairments. Various brain imaging techniques have been used to investigate the integrity of brain white matter (WM) and gray matter (GM) in these disorders. Despite promising preliminary findings, it is still unclear whether these alterations may be considered as common trait markers or may be used to distinguish BD from UD. A systematic literature search of studies between 1980 and September 2013 which reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 104 publications
5
74
0
Order By: Relevance
“…Alterations in CT in severe mental disorders, such as schizophrenia and BD, have been suggested as being due to a reduced number of synaptic contacts in affected areas (Harrison, 1999) or to neuronal apoptosis (Glantz et al, 2006). Our findings are in accord with several previous studies, which revealed that BD patients had more widespread WM abnormalities, GM volume reductions, and different aberrant functional connectivity in the neural circuits responsible for emotion regulation, attentional control, and reward-processing compared to MDD patients (Fung et al, 2015, Serafini et al, 2014). This is not surprising, given that BD is considered to be a more chronic illness and is associated with an earlier age of onset and more episodes of major depression compared with MDD (Merikangas et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Alterations in CT in severe mental disorders, such as schizophrenia and BD, have been suggested as being due to a reduced number of synaptic contacts in affected areas (Harrison, 1999) or to neuronal apoptosis (Glantz et al, 2006). Our findings are in accord with several previous studies, which revealed that BD patients had more widespread WM abnormalities, GM volume reductions, and different aberrant functional connectivity in the neural circuits responsible for emotion regulation, attentional control, and reward-processing compared to MDD patients (Fung et al, 2015, Serafini et al, 2014). This is not surprising, given that BD is considered to be a more chronic illness and is associated with an earlier age of onset and more episodes of major depression compared with MDD (Merikangas et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…This result is also consistent with several previous VBM studies. For example, Serafini et al (2014) reported reduced GM density in the left PTRI in BD patients, and Maller et al (2014) found two clusters with abnormal GM density in the PTRI which were correlated with HAMD scores in BD patients. Our finding provides evidence that the CT of the PTRI is correlated inversely with the number of depressive episodes in BD patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent major step forward in the field has been the realization that distributed brain connectivity rather than individual regions could underlie the pathophysiology of psychotic disorders 5 . Diffusion tensor imaging (DTI) studies reported more widespread white matter connectivity abnormalities in BD relative to MDD 2, 6, 7 . Intrinsic functional connectivity, a measure derived from resting-state fMRI (R-fMRI), has emerged as an effective tool for exploring large-scale human brain organization.…”
Section: Introductionmentioning
confidence: 99%
“…One population-based study rendered possible via linkage of records of three health data sets compared disordered (ADHD; n = 11,902) and non-disordered children (healthy controls; n = 27,304) under 18 years [11]. Two reviews, one on studies which reported white matter/gray matter changes in pediatric and adolescent bipolar disorder/unipolar depression, as detected by diffusion tensor imaging and voxel-based analysis [10], and the other providing an overview of ASD screening studies and ongoing programs across Europe [4], also report findings on large cumulated total samples of clinically diagnosed patients.But do studies with larger sample sizes result regularly in findings of higher quality or relevance?First, the advantages of a large sample size include a more precise estimate of the effect size and an easier assessment of the representativeness of the sample and the generalizability of the achieved results. However, a small effect size may not prove to be of clinical relevance.…”
mentioning
confidence: 99%
“…One population-based study rendered possible via linkage of records of three health data sets compared disordered (ADHD; n = 11,902) and non-disordered children (healthy controls; n = 27,304) under 18 years [11]. Two reviews, one on studies which reported white matter/gray matter changes in pediatric and adolescent bipolar disorder/unipolar depression, as detected by diffusion tensor imaging and voxel-based analysis [10], and the other providing an overview of ASD screening studies and ongoing programs across Europe [4], also report findings on large cumulated total samples of clinically diagnosed patients.…”
mentioning
confidence: 99%